SYNERGY BETWEEN PARENTS AND SCHOOL ROLES IN THE EDUPARK TOUR PROGRAM TO STRENGTHEN INDEPENDENCE AND ENVIRONMENTAL CARE VALUES AT SMP NEGERI 61 SURABAYA - Alya Fikriyah Dzihni Kusnanda; Sarmini; Segara Nuansa Bayu; Hendri Prastiyono (Jurnal Dialektika Pendidikan IPS, 2026)
The Edupark tourism program has great potential in instilling the values of independence and environmental awareness in students through direct and contextual experiences. The most significant challenge to be addressed is the limited involvement of parents in this program, which needs to be examined in order to strengthen collaboration between schools and parents. This study aims to analyze the synergy between the role of parents and schools in reinforcing the values of independence and environmental awareness among students of SMP Negeri 61 Surabaya through Edupark tourism activities, while also identifying the challenges and solutions that arise in the collaborative process. The research method employs a qualitative case study approach with subjects consisting of parents, the principal, and the Adiwiyata coordinator teacher. Data collection techniques include interviews, observations, and documentation. The findings show that the synergy between schools and parents in the Edupark tourism program takes the form of directed technical participation. However, this synergy has not yet reached a comprehensive deliberative collaboration, due to time constraints and the lack of two-way communication, which hinders collective understanding of the goals and challenges of the activities. Nevertheless, the school has made sustainable efforts by scheduling activities more flexibly on weekends and creating two-way dialogue spaces through WhatsApp channels. These research findings contribute theoretically to the development of collaboration concepts in the context of environment-based and community-based education.